2020
DOI: 10.1111/aas.13677
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin and the risk of bleeding after cardiac surgery

Abstract: Gelatin and other colloids, such as hydroxyethyl starch (HES), have been used in cardiac surgery because of their ability to preserve intravascular volume (ie plasma expanders) better than crystalloids. 1-3 They are also used to maintain blood pressure and avoid blood product transfusions. 2,3 Unfortunately, gelatin and HES have been associated with impaired coagulation and hemostasis. 4,5 Even a small dose of gelatin has been shown to impair clot strength and platelet adhesion in cardiac surgery. 6 However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This may well represent a chance finding, but gelatin’s deleterious effects on clot formation could also explain this, in part [ 18 20 ]. This finding also supports the results of a recent observational trial in cardiac surgical patients, whereby administration of gelatin was associated with increased chest drain output, bleeding events and red blood cell transfusion, compared to crystalloid fluid alone [ 43 ]. The effect of gelatin on coagulation and bleeding remains contentious [ 44 ], and this deserves further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…This may well represent a chance finding, but gelatin’s deleterious effects on clot formation could also explain this, in part [ 18 20 ]. This finding also supports the results of a recent observational trial in cardiac surgical patients, whereby administration of gelatin was associated with increased chest drain output, bleeding events and red blood cell transfusion, compared to crystalloid fluid alone [ 43 ]. The effect of gelatin on coagulation and bleeding remains contentious [ 44 ], and this deserves further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Postoperative bleeding following cardiothoracic procedures remains an important concern with multiple avenues of investigation continuing to assess factors predisposing and potentially influencing the severity of this adverse event. Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; 33 36 direct linkage of postoperative cardiac surgical bleeding with increased cost; 4 , 5 safe and efficacious use of postoperative fibrinogen concentrates; 37 , 38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39 , 40 transfusion reductions associated with the use of prothrombin complex concentrate; 41 , 42 morbidity associated with reoperation for bleeding following cardiac surgery; 3 , 43 , 44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45 , 46 contribution of albumin/gelatin to postoperative bleeding; 47 49 advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; 50 52 benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53 , 54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55 , 56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…The two recent large studies with adequate sample size are not randomized trials, which may have introduced bias into the results. Bearing this in mind, one study in cardiac surgical patients found that perioperative administration of succinylated gelatin was associated with a higher chest drain output, higher grades of bleeding, and more patients receiving red blood cell transfusions, compared to the use of crystalloid (133). The second observational report compared separate 2-year periods during which cardiac surgical patients received a majority of succinylated gelatin, low MW HES, or crystalloid in the perioperative period.…”
Section: Gelatinmentioning
confidence: 99%